2020
DOI: 10.3389/fcell.2020.593638
|View full text |Cite
|
Sign up to set email alerts
|

miR-140-5p in Small Extracellular Vesicles From Human Papilla Cells Stimulates Hair Growth by Promoting Proliferation of Outer Root Sheath and Hair Matrix Cells

Abstract: The application of dermal papilla cells to hair follicle (HF) regeneration has attracted a great deal of attention. However, cultured dermal papilla cells (DPCs) tend to lose their capacity to induce hair growth during passage, restricting their usefulness. Accumulating evidence indicates that DPCs regulate HF growth mainly through their unique paracrine properties, raising the possibility of therapies based on extracellular vesicles (EVs). In this study, we explored the effects of EVs from high- and low-passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…The loss of a cells loses defining characteristics is reflected in their EVs as well. This was demonstrated by Chen et al described earlier where the ability of EVs from low passage DPCs to stimulate hair growth in ORSCs and HMCs was lost at higher passage numbers ( Chen et al, 2020b ).…”
Section: Advantages and Disadvantages Of Cell-derived Nanovesicles Fo...mentioning
confidence: 58%
See 2 more Smart Citations
“…The loss of a cells loses defining characteristics is reflected in their EVs as well. This was demonstrated by Chen et al described earlier where the ability of EVs from low passage DPCs to stimulate hair growth in ORSCs and HMCs was lost at higher passage numbers ( Chen et al, 2020b ).…”
Section: Advantages and Disadvantages Of Cell-derived Nanovesicles Fo...mentioning
confidence: 58%
“…Further experiments showed that miR-140-5p targeted BMP2 expression; treatment with an miR-140-5p inhibitor abolished hair growth effects. This study showed that miR-140-5p from low passage number DPC-EVs impacts HF growth and hair cycling ( Chen et al, 2020b ). EVs derived from DPCs (DPC-EVs) on hair inductive gene expression in adipose derived stem cells (ADSCs)was investigated.…”
Section: Cell-derived Nanovesicles and Their Action Of Mechanism For ...mentioning
confidence: 97%
See 1 more Smart Citation
“…miRNA-140-5p is enriched in low-passage DPC exosomes and targets BMP-2, which promotes ORS and matrix cell proliferation. This suggests a potential clinical application of exosomes ( Chen et al, 2020 ).…”
Section: Roles Of Non-coding Rnas In Specific Parts Of the Hair Folliclementioning
confidence: 94%
“…They used RNA-sequencing to identify that extracellular matrix synthesis is increased in 3D culture DP cells, and set up a transcription factor–miRNA coregulatory network in this co-culture system, which may be beneficial for future AGA studies at the molecular level. In addition to the extracellular matrix, the same group also identified that miR-140-5p in small extracellular vesicles secreted by DP cells suppresses Bmp2 expression to promote proliferation of ORS and hair matrix cells in a co-culture model ( Chen et al, 2020 ). Tissue engineering models have been established to promote hair follicle neogenesis.…”
Section: Hair Follicle Stem Cell Regeneration In Agingmentioning
confidence: 99%